2018
DOI: 10.1093/cercor/bhy222
|View full text |Cite
|
Sign up to set email alerts
|

Early Developmental Trajectories of Functional Connectivity Along the Visual Pathways in Rhesus Monkeys

Abstract: Early social interactions shape the development of social behavior, although the critical periods or the underlying neurodevelopmental processes are not completely understood. Here, we studied the developmental changes in neural pathways underlying visual social engagement in the translational rhesus monkey model. Changes in functional connectivity (FC) along the ventral object and motion pathways and the dorsal attention/visuo-spatial pathways were studied longitudinally using resting-state functional MRI in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 105 publications
6
18
0
Order By: Relevance
“…Notwithstanding the above defense of GSR, we acknowledge that controversy regarding this method persists (Murphy & Fox, 2017). Because of this, we previously compared infant macaque FC with and without GSR and obtained similar results throughout development (Kovacs-Balint et al, 2018), including the current dataset, in which similar effects of maltreatment were detected on amygdala FC with and without GSR (Morin et al, 2015 ).…”
Section: Methodssupporting
confidence: 56%
See 3 more Smart Citations
“…Notwithstanding the above defense of GSR, we acknowledge that controversy regarding this method persists (Murphy & Fox, 2017). Because of this, we previously compared infant macaque FC with and without GSR and obtained similar results throughout development (Kovacs-Balint et al, 2018), including the current dataset, in which similar effects of maltreatment were detected on amygdala FC with and without GSR (Morin et al, 2015 ).…”
Section: Methodssupporting
confidence: 56%
“…mean ± standard deviation) and intubation, scans were collected under the lowest possible level of isoflurane anesthesia (1.0 ± 0.1%, inhalation; mean ± standard deviation) to minimize its reported dampening effect on blood oxygen level dependent (BOLD signal) (Hutchison, Womelsdorf, Gati, Everling, & Menon, 2013; Li, Patel, Auerbach, & Zhang, 2013; Miranda-Dominguez et al, 2014b; Tang & Ramani, 2016; Vincent et al, 2007). MRI images were acquired and processed following approaches optimized by our group for studies of macaque neurodevelopment (Kovacs-Balint et al, 2018; Mavigner et al, 2018) and protocols developed and widely used for macaques (Grayson et al, 2016; Hutchison et al, 2012; Li et al, 2013; Margulies et al, 2009; Sallet et al, 2011; Vincent et al, 2007). Our isoflurane levels are even lower than previously used in macaque studies of sensory, motor, visual, and cognitive-task related systems that reported patterns of coherent BOLD fluctuations similar to those observed in awake behaving monkeys (Vincent et al, 2007; Hutchison et al, 2013; Li et al, 2013; Miranda-Dominguez et al, 2014b; Tang & Ramani, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-one infant male rhesus monkeys (Macaca mulatta) were studied longitudinally as part of a larger project that also examined developmental trajectories of resting state functional brain connectivity ( Kovacs-Balint et al, 2019 ), white matter maturation (DTI), and social visual perception of relevance for ASD-deficits using eye-tracking ( Muschinski et al, 2016 ; Parr et al, 2016 ; Wang et al, 2020 ). Only males were studied due to the higher male:female ratio diagnosis of ASD ( Loomes et al, 2017 ; Baio et al, 2018 ) and other neurodevelopmental disorders, and to increase power for our analyses.…”
Section: Methodsmentioning
confidence: 99%